Wolf, Personalities And Problems - Interpretive Essays In World Civilizations; Moss, Terry, & Upshur, Eds., The Twentieth Century - Readings In Global History; Chan & Weiner, Eds., Twentieth Century International History - A Reader - Levinson, Daniel (Teaching History: A Journal of Methods, 2000)
Finding the right book of primary and secondary source readings for a history course is never an easy task. The selections might be too long or too short, overly focused on politics and personality, the right material pitched to the wrong grade level, good in one time period but weaker in another, useful but not interesting, etc. Teachers of world history have the additional problem of breadth vs. depth.